The Example of the Gracchi and Cicero's Publication of His Catilinarians - Pierzak, Damian (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2019)
The paper is a contribution to the ongoing scholarly debate on the possible editorial revision of Cicero’s consular orations. It focuses on one particular feature of the speaker’s rhetorical strategy, namely the use of the example of the Gracchi brothers. The analysis of three passages from the Catilinarians shows that some of Cicero’s references to the past tribunes of the plebs are more relevant to the political climate of 60 bce than to the original setting of the speeches. It is argued that, due to its various uses of the same historical exemplum, the text as we have it would be a good model for the aspiring orators and the students of rhetoric.
Keywords: Cicero